Analysis of pharmacy logistics planning and control using the pareto and balanced scorecard method at Bekasi District Hospital - R. Yuliyana Kusaeri; Eka Yoshida Syofian; Yanuar Jak (Science Midwifery, 2026)
Hospital pharmaceutical logistics management faces complex challenges where conventional planning methods often result in disparities between financial indicators and service quality. This study applies an integrated diagnostic approach combining ABC-Pareto analysis with Balanced Scorecard to reveal systemic performance gaps. Using a descriptive-analytical research design with mixed-methods approach, this research encompasses comprehensive analysis of 1,127 pharmaceutical products (January-December 2024 period) accompanied by extensive interviews with 20 strategic informants. Main findings reveal that ABC categorization identified 41 products (3.64%) in Category A contributing 80% of total value (IDR 12.8 billion), while 1,003 items (89%) showed zero ending balance—indicating substantial formulary expansion. BSC assessment revealed a fundamental contradiction: Financial dimension scored 76.67% (indicating adequacy) inversely proportional to Customer dimension at 59.38% (showing inadequacy)—with a 17 percentage point gap. Investigation identified three interrelated causal factors: formulary expansion eroding working capital allocation, procurement lead time variability requiring excessive safety stock accumulation, and ABC stratification that has been implemented but without operational execution. Unrecorded cost burden was calculated at IDR 4-6.7 billion annually (representing 3-5% of budget), including emergency procurement surcharges, drug substitution cost differentials, and lost opportunity costs. This study establishes that traditional measurement approaches create an 'illusion of adequacy' that masks underlying system dysfunction. Five empirically-based recommendations include: formulary optimization, operationalization of ABC framework enabling differentiated inventory control, systematic lead time performance tracking, expansion of financial measurement parameters, and integrated governance architecture.